2011
DOI: 10.3389/fnins.2011.00093
|View full text |Cite
|
Sign up to set email alerts
|

Two Independent Networks of Interstitial Cells of Cajal Work Cooperatively with the Enteric Nervous System to Create Colonic Motor Patterns

Abstract: Normal motility of the colon is critical for quality of life and efforts to normalize abnormal colon function have had limited success. A better understanding of control systems of colonic motility is therefore essential. We report here a hypothesis with supporting experimental data to explain the origin of rhythmic propulsive colonic motor activity induced by general distention. The theory holds that both networks of interstitial cells of Cajal (ICC), those associated with the submuscular plexus (ICC–SMP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
136
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 129 publications
8
136
4
Order By: Relevance
“…30 Also in the rat colon, the strongest myogenic pacemaker originates in the ICC-SMP, which is governing the ripples at 10-14 cpm, which can be seen to be part of all the motor patterns. 19,21,22,[31][32][33] They are clearly seen in the most proximal colon in between the LDCs in Figure 3B. They do not appear to be associated with the slow propagating segmental contractions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…30 Also in the rat colon, the strongest myogenic pacemaker originates in the ICC-SMP, which is governing the ripples at 10-14 cpm, which can be seen to be part of all the motor patterns. 19,21,22,[31][32][33] They are clearly seen in the most proximal colon in between the LDCs in Figure 3B. They do not appear to be associated with the slow propagating segmental contractions.…”
Section: Discussionmentioning
confidence: 79%
“…In the small intestine, the classical segmentation motor activity is generated when the ICC associated with the deep muscular plexus (ICC-DMP) produce a stimulus-dependent rhythmic electrical activity. 34,35 In the rat colon, it is the ICC-MP that generates a stimulus-dependent low frequency activity; the laboratories of Jimenez in the rat 31 and Takaki in the mouse 36 showed that ICC-MP are associated with a low frequency pacemaker that can drive contractions at frequencies from 0.3 to 2 cpm, 19,21,22,[31][32][33] hence the on/off pattern observed in the present study is likely to be associated with pacemaking from the ICC-MP. It is not known where the ultra-slow pacemaker that drives the slow propagating segmental contractions is located; it may be within the ENS or in the intramuscular ICC (ICC-IM).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While these patterns were identified by earlier experimental methods, the current approach allows a more refined definition of localized contractile movements such as ripples and novel antiperistaltic contractions 9,24,25,30,31,42 . The construction of STmaps and analysis of changes in motility pattern have been applied to key questions in the gastrointestinal motility of intestine and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Video recording and spatiotemporal mapping of intestinal and colonic segments have been applied to a variety of species including zebrafish 26 , mouse 25,[27][28][29][30] , rat 7,9,[30][31][32][33] , guinea pig 5,6,8,[13][14][15][16][17][18][19]24,30,32,34,35 , brushtail possum 12,36 , rabbit 2,30,37,38 , chicken 39 , pig 40,41 and human 42 . The most widely studied species is the guinea pig.…”
Section: Discussionmentioning
confidence: 99%